Explosion characteristics of cyclic hydrocarbon-air mixtures at elevated temperature and pressures. (1st October 2019) - Li, Qianqian; Yan, Zhiyu; Lin, Wenjun; Zhao, Haoran; Liu, Hu; Huang, Zuohua
Highlights: Explosion parameters of five cyclic hydrocarbon-air mixtures were determined. The effects of initial conditions on explosion properties were presented. The effect of unsaturation degree on explosion properties was interpreted. Exponential correlations were established between explosion index and explosion phasing parameters. Abstract: Explosion characteristics of cyclic hydrocarbon (cyclohexane, cyclohexene, 1, 3-cyclohexadiene, 1, 4-cyclohexadiene, benzene)-air mixtures were experimentally investigated in a closed vessel at the temperature of 403 K and pressures of 0.1 and 0.5 MPa. These fuels own different degrees of unsaturation. The crucial explosion parameters were determined, including explosion pressure, rate of pressure rise, explosion index as well as explosion delay. Results indicate that the peak explosion pressure and maximum rate of pressure rise all increase with the rise of initial pressure, demonstrating the high explosion risk at elevated pressure. Except benzene-air mixture, the more unsaturated cyclic hydrocarbon-air mixture has higher values of peak explosion pressure, maximum rate of pressure rise as well as explosion index, and lower values of explosion delay and burn period. Therefore, cyclohexadiene-air mixtures propagate the fastest and show the greatest potential explosion hazard. Cyclohexane-air mixture propagates the slowest and shows the smallest explosion potential as well. This is mainly caused by the different heat release of the cyclic fuel flames. The peak explosion pressure and maximum rate of pressure of benzene-air mixture are between those of cyclohexadiene- and cyclohexane-air mixtures at the lean to slightly rich conditions, while present the lowest values at the extremely rich conditions. This is attributed to the high tendency of soot formation in benzene flame and thus enhanced heat radiation to the vessel wall. Such heat loss also contributes the extended explosion delay and burn period of benzene-air mixture. Furthermore, the explosion index could be correlated with the explosion delay and burn period in exponential expression. This exponential relationship was found to be feasible for methanol-air mixture as well.